Three-dimensional assessment after maxillary sinus grafting with a bovine, a porcine, and a synthetic bone substitute material. A randomized controlled clinical trial. - Schmitt, Christian; Wiesheu, Simon; Schlegel, Karl Andreas; Adler, Werner; Kesting, Marco Rainer; Matta, Ragai; Möst, Tobias (International Journal of Computerized Dentistry, 2024)
AIM: The present randomized controlled clinical trial focused on graft volume alterations after sinus floor augmentation with a deproteinized bovine bone mineral (DBBM; Bio-Oss), a deproteinized porcine bone mineral (DPBM; THE Graft), or a biphasic calcium phosphate (BCP; Osopia) material. MATERIALS AND METHODS: A total of 28 patients with edentulism in the posterior maxilla with ≤ 5 mm of residual bone height received a two-staged external sinus grafting procedure with DBBM, DPBM, or BCP. Three CBCT scans were performed: 1) prior to surgery (CBCT1); 2) directly after surgery (CBCT2); 3) after a healing period of 4 to 6 months, prior to implant placement (CBCT3). The CBCT scans were used to analyze volumetric alterations of the sinus grafts by virtual 3D model matching of CBCT1 and CBCT2 (situation after sinus grafting), and CBCT1 and CBCT3 (situation prior to implant placement). RESULTS: The volume of the bone graft in the maxillary sinus (volume [VOL%] directly after grafting rated as 100%) was stable after the healing period in the DBBM (VOL%: 103 ± 4%) and the DPBM (VOL%: 112 ± 23%) groups, with no statistically significant differences regarding 3D measurements. In the BCP group, the grafted volume declined to VOL%: 66 ± 25%, statistically inferior to the DBBM and DPBM groups. CONCLUSIONS: Regarding bone graft stability/volume, the DBBM and DPBM groups showed comparable outcomes. Due to resorption, the BCP group showed inferior bone graft volume after healing (statistically significant) compared with the DBBM and DPBM groups.
EVALuna2:541030